The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.juro.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Infection Retardant Coated Inflatable Penile Prostheses Decrease the Incidence of Infection: A Systematic Review and Meta-Analysis

Abstract: This analysis documents a significant advantage of using coated compared to noncoated inflatable penile prostheses to prevent postoperative device infection. Infection retardant coatings that allow antibiotics to elute off the device components decrease the incidence of device infection by approximately 50%. Future studies must address novel techniques, such as preventing bacterial adhesion, to further decrease infectious etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…15 A potential rationale for this dramatic switch from MPs to IPPs in the last 10 years could be credited to the enhancement of IPPs with infection retardant coatings, which have decreased the infection rate by 50%. 16,17 Future studies of which patients are still receiving a MP may provide insight into the decision making process for urologists.…”
Section: Discussionmentioning
confidence: 99%
“…15 A potential rationale for this dramatic switch from MPs to IPPs in the last 10 years could be credited to the enhancement of IPPs with infection retardant coatings, which have decreased the infection rate by 50%. 16,17 Future studies of which patients are still receiving a MP may provide insight into the decision making process for urologists.…”
Section: Discussionmentioning
confidence: 99%
“…With the latest devices and techniques, those rates have effectively halved [29]. Mandava et al reported primary implant infection rates with non-coated at 2.32% and coated IPPs at 0.89% [30]. Another study reported coated primary implant infection rates of 0 of 223 in non-diabetic patients and 1% for diabetic patients.…”
Section: Current Infection Ratesmentioning
confidence: 99%
“…Despite careful work and the use of copious antibiotic irrigation of the implant space and systemic prophylactic antibiotics, the incidence of infection ranges between 1% and 6.5% (1, 8). These rates may further decline by 50% with the use of drug-coated prostheses for both first-time and repeat implantations (9, 10). Although infection rates are low, morbidity due to infection is serious.…”
Section: Introductionmentioning
confidence: 99%